Application Design for Food and Beverage Online Delivery System Based of Android Framework - Abdul Manan; Victor Wiley; Thomas Lucas (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2019)
Providing good services and satisfaction to customer is main concern on online business. As technology is developed rapidly, many online restaurants has sought user-friendly platform to serve their customer. The purpose of this research is to build an Android-based online order application for online delivery restaurant. We added features of outlets distribution and product promos. We also developed a more user-friendly interface as new design. Through Waterfall development method, we design the application which based of android APP Inventor framework. Based on the assessment result of four aspect (e.g., software engineering defect, learning design, visual communication), we got average scores of 2.45, 3.40, 3.35 and 3.07. The assessment results showed that our application design is eligible to be implemented for real situation with fairly eligible score. It is recommended that the application is implemented with partial improvement especially on the software engineering debugging to get a more decent score.